Randomized Controlled Trial: Prophylactic Autologous Fascia Sling for Women at Risk of Urethral Incontinence after Obstetric Fistula Repair (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To compare sling types as anti-incontinence procedure for women with obstetric fistulas at high-risk for residual incontinence.Methods: This is a multiple-site randomized controlled trial comparing autologous fascia slings to pubococcygeal (PC) slings at time of fistula repair. Participants with a Goh type 3 or 4 vesico-vaginal fistula (urethral length